Anharmonic phonon decay in cubic GaN - Cuscó, R.; Domènech-Amador, N.; Novikov, Sergei V.; Foxon, C. Thomas; Artús, L. (American Physical Society, 2015)
We present a Raman scattering study of optical phonons in zincblende (cubic) GaN for temperatures ranging from 80 to 750 K. The experiments were performed on high quality, cubic GaN films grown by molecular beamepitaxy on GaAs (001) substrates. The observed temperature dependence of the optical phonon frequencies and linewidths is analyzed in the framework of anharmonic decay theory, and possible decay channels are discussed in the light of density-functional theory calculations. The LO mode relaxation is found to occur via asymmetric decay into acoustic phonons, with an appreciable contribution of higher order processes. The TO mode linewidth shows a weak temperature dependence and its frequency downshift is primarily determined by the lattice thermal expansion. The LO phonon lifetime is derived from the observed Raman linewidth and an excellent agreement with previous theoretical predictions is found